Antioxidant, xanthine oxidase (XO) inhibitory, hypouricemic effect evaluation and GCMS analysis of ethanolic extract of Piper chaba stem: Supported by in vitro, in vivo, and molecular docking experiments - Sahria Rahman; Umme Kulsum Hridy; Marjana Alam; Rahima Begum; Md Arju Hossain; Kishore Kumar Sarkar; Kamalesh Saha; Apurba Kumar Barman; Nripendra Nath Biswas (Elsevier, 2024)
Background: Piper chaba has been traditionally using for its potential health benefits. The principal goal of this investigation was to assess the pharmacological characteristics of the EEPCS, focusing on investigating its potential antihyperuricemic effects, ability to inhibit xanthine oxidase (XO) enzyme, and antioxidant properties. Methods: The antioxidant capability of the extract was assessed using the DPPH radical assay. The extract was evaluated in vitro aimed at its xanthine oxidase inhibitory (XOI) action and further experimented for its antihyperuricemic effect on the Potassium oxonate (PO) induced hyperuricemia murine model. Besides, molecular docking techniques were employed to interpret the inhibitory mechanism of the compounds identified through GCMS analysis of the EEPCS. Results: There was no safety concern at doses up to 3000 mg/kg of the extract as confirmed by mice model studies. The extract displayed potent the antioxidant properties during quantitative antioxidant test (IC50=104.9 ± 0.99 µg/mL). In XOI test, the extract was found to be effective with an IC50 value of 26.14 μg/mL. In addition, the extract was found to decrease the Serum uric acid (SUA) levels by 36.72 and 61.84 % at 100 and 200 mg/kg body weight respectively, compared to the hyperurecaemic animals. The GCMS analysis of the extract revealed eighteen distinct compounds, which were docked against human peroxiredoxin 5 and xanthin oxidase proteins. Selina-3,7(11)-diene (CID: 6429221) was the most effective phytochemical for the human peroxiredoxin 5 protein having binding score −6.2 Kcal/mol compared to standard ascorbic acid (5.6 Kcal/mol). Besides, gamma-muurolene (-7.9 Kcal/mol) was the most effective phytochemical for the XO protein compared to standard allopurinol (−6.4 Kcal/mol). Conclusion: Our experimental data showed that the EEPCS has potentiality as an antioxidant and hypouricemic agent that could be contributed to treat and manage oxidative stress (OS), gout and hyperuricemia.